Risk factors in patients with perimesencephalic hemorrhage. (15th March 2014) - Mensing, L. A.; Ruigrok, Y. M.; Greebe, P.; Vlak, M. H. M.; Algra, A.; Rinkel, G. J. E.
<x xml:space="preserve">Abstract</x> Background and purpose Smoking and hypertension are risk factors for aneurysmal subarachnoid hemorrhage (aSAH), whilst excessive alcohol consumption is less consistently linked with aSAH. Perimesencephalic hemorrhage (PMH) is a benign subset of non‐aneurysmal subarachnoid hemorrhage. The exact cause of PMH is unknown, and its risk factor profile may help to elucidate the pathogenesis. The influence of smoking, hypertension and excessive alcohol consumption on the occurrence of PMH was studied. Methods Seventy‐nine patients admitted with a PMH to the University Medical Center Utrecht were studied. As controls 574 persons were selected from five different general practices in the referral region of the University Medical Center Utrecht. All participants filled in a questionnaire about smoking habits, the presence of hypertension and alcohol consumption before their hemorrhage. Odds ratios (ORs) with corresponding 95% confidence intervals (CIs) were calculated to assess the association of risk factors and PMH, and multivariable logistic regression was used to adjust for possible confounding by age and sex. Results Adjusted ORs for the occurrence of PMH were 1.7 (95% CI 1.0–2.8) for smoking cigarettes, cigars, pipes or any combination of these, 1.1 (95% CI 0.6–2.0) for hypertension and 1.1 (95% CI 0.5–2.1) for excessive alcohol consumption. Conclusions Similar to aSAH, smoking is a risk factor for PMH and excessive alcohol consumption is not. In contrast to aSAH, hypertension is not a risk factor for PMH. This implies that the pathophysiological mechanisms causing PMH might be slightly different from those causing aSAH.